Initial cancer treatment and survival in children, adolescents, and young adults with Hodgkin lymphoma: A population‐based study. Issue 24 (8th September 2021) - Kahn, Justine M.; Maguire, Frances B.; Li, Qian; Abrahão, Renata; Flerlage, Jamie E.; Alvarez, Elysia; Keegan, Theresa H. M.
Abstract : Background: Hodgkin lymphoma (HL) is a treatable tumor affecting children, adolescents and young adults (AYAs; 15‐39 years old). Population‐based studies report worse survival for non‐White children and AYAs but have limited data on individual therapeutic exposures. This study examined overall and HL‐specific survival in a population‐based cohort of patients while adjusting for sociodemographic factors and treatment. Methods: Data for 4807 patients younger than 40 years with HL (2007‐2017) were obtained from the California Cancer Registry. Individual treatment information was extracted from text fields; chemotherapy regimens were defined by standard approaches for pediatric and adult HL. Multivariable Cox models examined the influence of patient and treatment factors on survival. Results: At a median follow‐up of 4.4 years, 95% of the patients were alive. Chemotherapy differed by age, with 70% of 22‐ to 39‐year‐olds and 41% of <22‐year‐olds receiving doxorubicin, bleomycin, vinblastine, and dacarbazine ( P < .001). In multivariable models, older patients (22‐39 vs < 21 y; hazard ratio [HR], 1.53; 95% confidence interval [CI], 1.11‐2.10), Black (vs White patients); HR, 1.90; 95% CI, 1.25‐2.88), and Hispanic patients (HR, 1.45; 95% CI, 1.06‐1.99) experienced worse survival; among those < 21 y, Black race was associated with a 3.3‐fold increased risk of death (HR, 3.26; 95% CI, 1.43‐7.42). Conclusions: In children and AYAs with HL, older age and non‐White race/ethnicity predicted worse survival after adjustments for treatment data. Further work is needed to identify the biological and nonbiological factors driving disparities in these at‐risk populations. Abstract : Adjusting for chemotherapy regimen and treatment details in this population‐based cohort does not mitigate survival differences by age, with adolescents and young adults being more likely to die than children with Hodgkin lymphoma. In Black children (vs White children), the risk of death from Hodgkin lymphoma is increased up to 5‐fold even after adjustments for detailed treatment data.